ABOUT WORK IN PROGRESS IN THE CONTEXT OF INTRALOGISTICS: ABOUT WORK IN PROGRESS IN THE CONTEXT OF INTRALOGISTICS - Stoyanov, Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The current paper attempts, briefly and in general terms, to present the need for work-in-progress for the normal flow of the production process. This ensures the rhythmicity and continuity of the flow of production. The basis for achieving these two characteristics is also the so-called reserve, which should be in sufficient quantity.